Mode of Inheritance and Interrelationship among Age at First Egg, Body Weight at First Egg and Weight of First Egg in Local by Exotic Inbred Chicken Crosses - Udeh, I. (International Journal of Poultry Science, 2010)
The interrelationship among Age at First Egg (AFE), Body Weight at First Egg (BWFE) and Weight of First Egg (WFE) and their inheritance were studied in the F1 crossbred groups generated from the mating of inbredlines of two exotic and the local chickens. The birds were reared on deep litter pens from day old to 24 weeks of age when all the groups had started laying. The results indicated that the F1 crossbred groups differed significantly (p<0.01) with respect to AFE, BWFE and WFE. Sire influence as well as non additive genetic effects were responsible for the inheritance of AFE of the crossbred groups while their BWFE were controlled by the dominant genes transmitted from the exotic parent. It was also observed that WFE of the crossbred groups were influenced by both additive and dominance gene actions. The results further showed that BWFE and WFE were closely related in all the F1 crossbred groups while correlated responses were found among AFE, BWFE and WFE only in the combined F1 crosses of the local and pure black groups. The implication of this result was that selection for any of these traits could give positive response to others.